2019
DOI: 10.1126/science.aau9460
|View full text |Cite
|
Sign up to set email alerts
|

Herbivores as drivers of negative density dependence in tropical forest saplings

Abstract: Ecological theory predicts that the high local diversity observed in tropical forests is maintained by negative density–dependent interactions within and between closely related plant species. By using long-term data on tree growth and survival for coexisting Inga (Fabaceae, Mimosoideae) congeners, we tested two mechanisms thought to underlie negative density dependence (NDD): competition for resources and attack by herbivores. We quantified the similarity of neighbors in terms of key ecological traits that me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
115
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(121 citation statements)
references
References 60 publications
4
115
2
Order By: Relevance
“…refs. 57,58 ), on the basis of the evidence presented here, insects and plant-associated fungi appear to play a greater role in mediating conspecific density dependence than large herbivores.…”
Section: Discussionmentioning
confidence: 68%
“…refs. 57,58 ), on the basis of the evidence presented here, insects and plant-associated fungi appear to play a greater role in mediating conspecific density dependence than large herbivores.…”
Section: Discussionmentioning
confidence: 68%
“…A recent experimental study, which looked at monocultures vs. mixed seedlings exposed to drought, suggested that competition for water in drought environment was reduced in more diverse neighborhoods (O'Brien et al 2017). However, this probably cannot be used to explain the patterns we found as competition for limiting resources has been considered to be weak to nonexistent in diverse forests (Paine et al 2008, Forrister et al 2019. A third possibility is that the effects of the surrounding neighborhoods tell more about local habitat heterogeneity than biotic interactions (Comita and Hubbell 2009).…”
Section: Discussionmentioning
confidence: 91%
“…, Forrister et al. ). A third possibility is that the effects of the surrounding neighborhoods tell more about local habitat heterogeneity than biotic interactions (Comita and Hubbell ).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible though that the duration of our study was insufficient to pick up the effects of insects and fungal enemies on established seedlings, which may occur over longer time scales. For example, insect herbivores can alter survival and growth of older seedlings and saplings (Forrister et al, 2019), but these effects may take years to manifest, particularly in terms of aggregate community responses such as diversity or composition. Similarly, fungi infect established seedlings and saplings and impact their growth and survival (Gilbert and Webb, 2007), and foliar fungal infection and associated plant performance can be altered by fragmentation (Benitez-Malvido et al, 1999;Benítez-Malvido et al, 2018).…”
Section: Edge Effects On Insect and Fungal Regulation Of Seedling DIVmentioning
confidence: 99%